(untitled) (Nigerian Journal of Technology, 2008)
The potentials of cassava flour as a set-retarding admixture in concrete were investigated. Concrete mix proportion of 1:2:4 by weight of cement, sand and coarse aggregate and, water/cement ratio of 0.46 was made with six different dosage levels of cassava flour as admixture. The properties tested include setting time, workability of the fresh concrete and compressive strength of the hardened concrete. These properties were compared with those of similar concrete mix made without cassava flour admixture. It was observed that cassava flour considerably improved the workability of the fresh concrete and delayed the setting time of cement by up to 6 hours. Results of the tests also show that while cassava flour reduced the early strength of concrete, the long-term strength was improved. Cassava flour dosage level of 3% was also found to be the optimum level of addition of the admixture.